Helping to protect the future for farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Geographical indications are an effective tool for protecting agricultural products and foods associated with a specific region. The European Union, a pioneer in this sector, has long understood its potential. ACP countries are beginning to catch on in or